Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1021/ic901014r
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Dimetallic Gold Hydride Complex Stabilized by a Xantphos-Phosphole ligand: Synthesis, X-ray Crystal Structure, and Density Functional Theory Study

Abstract: The bis-2,5-diphenylphosphole xantphos ligand (XDPP) 1 reacts with the [AuCl(tht)] complex to afford the monocoordinated [Au(XDPP)Cl] 2 and the dicoordinated chelate species [Au(XDPP)Cl] 3. Addition of AgOTf on this mixture, at room temperature, affords the cationic [Au(XDPP)][OTf] complex 4 which was fully characterized. An X-ray crystal structure analysis confirms the bent structure of this 14 VE [ML(2)](+) complex. Reaction of 4 with HSiMe(2)Ph in tetrahydrofuran at -78 degrees C yields the dinuclear [(XDPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 51 publications
3
43
0
Order By: Relevance
“…[12] Using this mixture of gold chloride complexes was not a suitable way to test the catalytic reaction. On the other hand, a single cationic complex, 3-BF 4 , was obtained from the mixture upon chloride abstraction by the silver salt AgBF 4 [Eq.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[12] Using this mixture of gold chloride complexes was not a suitable way to test the catalytic reaction. On the other hand, a single cationic complex, 3-BF 4 , was obtained from the mixture upon chloride abstraction by the silver salt AgBF 4 [Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Nuclear magnetic resonance spectra were recorded on a Bruker AC-300 SY spectrometer operating at 300. [18] 2-OTf, [12] and 3-OTf [12] were prepared as reported previously. [AuClA C H T U N G T R E N N U N G (tht)] was prepared according to the established procedure.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…33 The 2 H NMR chemical shift of [(XDPP)Au-H-Au(XDPP)] þ complex (XDPP: bis-2,5-diphenylphosphole xantphos ligand) and the electronic structure of the [(XDPP)Au-H-Au(XDPP)] þ complex were studied through DFT calculations. 34 It was revealed that the hydride interacts in a bonding way with the s MO between the two Au atoms and in an antibonding way with a combination of d orbitals at the metal centres. 2 H, 1 H, 19 F and 15 N NMR spectra of CNHF-as an ion pair with a tetrabutylammonium cation dissolved in CDF 3 -CDF 2 Cl mixture were recorded in the slow exchange regime at temperatures down to 110 K and the fine structure due to spin-spin coupling of all nuclei involved in the hydrogen bridge was resolved.…”
Section: Shielding Of Particular Nuclear Speciesmentioning
confidence: 99%